Avaliação in situ da eficácia de um gel contendo catequina e nanopartículas de sílica mesoporosa na proteção da erosão de dentina radicular - Alves, Helaine Cajado (2019)
Dental erosion is a clinical condition of high prevalence in the world population. Due to aging population, lifestyle and eating habits, this condition has a tendency to increase over the years and represents a common complaint among patients. The aim of this study was to evaluate in situ the anti-erosive effect of gels containing epigallocatechin-3-gallate (EGCG) isolated and adsorbed on mesoporous silica nanoparticles (EGCG / NSM) on the wear and hardness of human root dentin. Dentin blocks were selected according to the initial surface hardness and randomly distributed in one of four groups (n = 11): placebo (control), SnF2 (0,05% -positive control), EGCG (0,1%) and NSM / EGCG (0,093%). Eleven volunteers participated in this randomized, controlled, cross-over study with 4 phases of 5 days each. They wore an acrylic palatal device containing 2 blocks of dentin that were treated with one of the gels. During each experimental phase, the specimens were subjected to erosion by immersion in citric acid (0,05M; pH 3,75) for 60s, 4 times a day, followed by treatment with the predetermined gel for 60s. The dentin alterations were determined by the percentage of surface hardness loss (% SHL) and profilometry analysis. Data were analyzed by ANOVA at one factor, followed by Tukey's post-test. About the% PDS, there was no statistical difference between the groups (p = 0,067). As for surface wear, the following results were obtained in micrometers: 0,66 (± 0,38); 0,57 (± 0,11); 0,48 (± 0,05) and 0.32 (± 0,08) for the placebo, EGCG, EGCG/NSM and SnF2 groups, respectively. Significant difference was observed only for the SnF2 group when compared to placebo and EGCG (p = 0,003 and p = 0,046). However, there was no significant difference between SnF2 and EGCG/NSM (p = 0,306). Therefore, the findings suggest that the use of EGCG/NSM is a promising protective measure in reducing dentin wear under erosive conditions.